PENINGKATAN AKTIVITAS BELAJAR SISWA MELALUI LESSON STUDY DI SMP PGRI 4 PONTIANAK - Ittihadi, Ses Muharman; Rif at, Muhammad; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve student learning activities through Lesson Study on rectangular material. The research was conducted at SMP PGRI 4 Pontianak Class VII semester 1 academic year 2011/2012 where the subject of this research is the students of class VII A which amounted to 35 people, with the details of 16 men and 19 women. The research used is Classroom Action Research (PTK). The study was conducted in two meetings. Each meeting consists of three stages, namely the stage of planning, implementation and reflection. The types of data collected in each cycle are quantitative data in the form of field research notes. Based on the observations obtained at each meeting, it can be seen that the more days learners become more active in learning activities. With the use of Lesson Study the classroom atmosphere becomes more alive and not monotonous, so that learners become more motivated, interested, and more active to follow the learning activities of mathematics. At the first meeting, the learning activities of students who support the learning there are 18 points while the learning activities of students who do not support learning there are 16 points. In the second cycle, student learning activities that support learning there are 23 points whereas student learning activities that do not support learning there are 10 points. The results showed that the Lesson Study can improve the learning activity of VII students of SMP PGRI 4 Pontianak. Keywords: inprove, activities, lesson study